DESIGN AND DEVELOPMENT OF PHYDROMOD APPLICATION USING SCIENCE PROCESS SKILLS APPROACH AT IBNU SINA UNIVERSITY (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2023)
The purpose of this research is to develop a Phydromod product which is an android-based physics practicum e-module. This is because the physics practice courses at the Faculty of Engineering, Ibnu Sina University (UIS) has a fundamental obstacle, namely there is no fixed module that guides all students like other universities and high student mobility. The method used in this study is the Research and Development (RnD) method by following the ADDIE model for module and Waterfall for aplication. Phydromod was developed using the Java program, which will later contain practicum modules for each meeting. The subjects in this study were 1C Regular Industrial Engineering students. The evaluation was carried out using two questionnaires which were analyzed using a Likert scale, which consisted of a module validation questionnaire and the phydromod application. The results of this study are in the form of module products with a module validation value of 88 and 88.2% Phydromod implementation.Keywords: e-modul, physics, android, application